Current problems of civil participation in the implementation of local government in Russia - S. S. Hamidov (Управление)
The main problems of the modern institution of civil participation in the implementation of local government in Russia have been analyzed in the article. Modern effective tools and processes, in the context of “civil participation” have been described. A number of issues and problems of formation of the institute of local government has been considered The democratic nature of the local government implies, the principle of transparency of the decisionmaking system at the local level and high level of trust of the population to local governments. Based on the study of processes, taking place in the country, as well as the analysis of scientific literature on civil pariticpation issue, the author highlights the factors, influencing the level of public confidence in the activities of local governments and the decision-making process by actors in the process of interaction between the authorities and society, in terms of ensuring the democratic nature of the local power.The aim of the analysis of the process of building the system of local government, under which social activity and civil participation in the implementation of the local government requires an interdisciplinary approach - to develop effective solutions and technologies of work with citizens, local authorities, that will lead to increased transparency in decision-making and enhance public confidence in the local authorities. In consideration, that developed institute of civil participation is a complex institution, which is an indicator of the democratic principle of organization of power, at the same time requiring a more thorough analysis of the type of relationship the actor process of interaction of authorities and society and their objectives, the author puts forward several theories, whereby you can ensure the effectiveness of the process of “participation”, in the context of mainstreaming, as described by the author.In the same way modern and effective tools and techniques have been described in the article, the application of which, according to the author, will lead to greater transparency in the work of local government authorities.